National health coverage programs and quality of referral obstetrics and gynaecology clinic in Dr Cipto Mangunkusumo Hospital Jakarta - Eka Rusdianto Gunardi; Arresta Vitasatria Suastika; Hanevi Djasri; Adi Utarini (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Purpose: Implementation of national health coverage contributes to the increasing number of outpatient visits in Obstetrics and Gynecology Department, Dr. Cipto Mangunkusumo Hospital. It may be caused by improper referral system or number of government insurance patients called as BPJS patients. Therefore, this study aims to analyse the pattern and quality of referral system in the implementation of national health coverage.Method: The quasi experimental study was conducted using pre and post analysis of the cases pattern and referral quality. It included accuracy of referred case diagnosis, accuracy of referring health facility, and consistency of referred case diagnosis.Results: There was an increasing number of referral visits in the early implementation of national health program; however, it declined overtime. There was reduction of general obstetrics and gynaecology cases and increase of sub-specialistic cases. It was in appropriate to the role of centre referral hospital in Indonesia. Around 98% referral diagnosis was correct to be referred, 82% cases came from correct health facility, and 98% referral diagnosis was consistent to Dr. Cipto Mangunkusumo hospital.Conclusion: The quality referral cases improves with the implementation of national health coverage program.